2016
DOI: 10.1111/jep.12522
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a structured prescription form improves the quality of handwritten prescriptions in limited resource setting of developing countries

Abstract: Structuring a prescription form alone may improve certain aspects of quality of written prescription in terms of completeness and legibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The quality of drug care provided to patients is largely dependent on the quality of the medical prescription [1]. Unfortunately, prescribers attach in general, little importance to the quality of the drafting of their medical prescriptions, while these are supposed to be the basis of the good medication of their patients [2]. The medical prescription is an act sufficiently legislated given its importance and must hence be written accurately, completely and legibly [3].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of drug care provided to patients is largely dependent on the quality of the medical prescription [1]. Unfortunately, prescribers attach in general, little importance to the quality of the drafting of their medical prescriptions, while these are supposed to be the basis of the good medication of their patients [2]. The medical prescription is an act sufficiently legislated given its importance and must hence be written accurately, completely and legibly [3].…”
Section: Introductionmentioning
confidence: 99%
“…In resource-limited settings where integrated computer systems are not readily available, introducing a structured prescription form may improve the quality of handwritten prescriptions in terms of completeness as well as legibility. 9 To this end, the prevalence of prescription errors at tertiary health-care facilities in the Hail region, Saudi Arabia was alarmingly high. 10 Studies examining completeness and legibility of handwritten prescriptions in Sana'a, Yemen indicated that the quality and completeness of prescriptions was found to be very poor.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, health care professionals must continually updated their knowledge on drug prescription, dosages, risks, and side effects 3 . However, according to the World Health Organization (WHO), more than half of these drugs are prescribed and dispensed inappropriately 4 .…”
Section: Introductionmentioning
confidence: 99%